Agroclimatic potential of sunflower in Paraiba State, Brazil. I. Temperature and solar radiatio - Zaffaroni, Eduardo; Silva, Marcos A. V.; de Azevedo, Pedro V. (Pesquisa Agropecuaria Brasileira, 1994)
The objective of this research was to analyse temperature and solar radiation in determining the best date of planting for sunflower in Paraíba State, Brazil. Two or three sites of each of the 12 homogeneous micro-regions (HMR) of the State were selected. Data of monthly mean temperature and mean solar radiation, and temperature index (TI) for sunflower were used to establish the growth index GI (product of phototermal quotient and TI). The GI and the relative ground cover were used to determine the accumulated crop growth index (AGI). Months with maximum AGI were considered as the most suitable planting dates for sunflower on the selected sites of the 12 HMR of Paraíba State, in the absence of water deficit. It was found that, for irrigated conditions, the best planting time for sunflower in Paraíba State would be from July to August for most of HMR.